Functional connectivity profiles of amygdala subregions in posttraumatic stress disorder - Elizabeth M. Haris; Richard A. Bryant; Kim L. Felmingham; Leanne M. Williams; Mayuresh S. Korgaonkar (Translational Psychiatry)
Abstract The amygdala is crucial to understanding posttraumatic stress disorder (PTSD), yet knowledge of the connectivity of its substructures and their contribution to the functional heterogeneity characteristic of the disorder remains limited. This study sought to delineate the functional profiles of amygdala substructures to advance a more nuanced understanding of their contribution to the neural circuitry underlying PTSD in a large sample. Task-derived intrinsic functional magnetic resonance imaging (rs-fMRI) data for 64 non-trauma-exposed controls (NEC) and 65 individuals with PTSD were analyzed. Amygdala subnuclei were segmented using FreeSurfer and combined into three major substructures for each hemisphere: the basolateral (BLA), centromedial (CMA), and superficial (SFA) nuclei. Seed-to-voxel functional connectivity analyses for the whole brain were performed to investigate group differences in subnuclei connectivity profiles. A significant group by subnuclei interaction was found for four clusters, driven by group differences in connectivity related to the BLA. There was lower connectivity in the PTSD group for the left BLA and precuneus, posterior cingulate, right superior parietal lobe, right postcentral gyrus, and bilateral precentral gyri. Higher connectivity was found in the PTSD group for the left BLA and brainstem, and for the right BLA and cerebellum, and brainstem and right pallidum. No group differences were found for the CMA or SFA. These results illustrate the importance of the BLA in driving task-derived intrinsic functional connectivity between NEC and PTSD groups. Findings suggest that group differences lie in lower connectivity with cortical areas involved in self-referential and sensorimotor processing, but higher connectivity with subcortical areas involved in arousal, salience, sensory, and reward processing.